Feminism in Nikewomen, What are girls made of Advertisement: a Multimodal Critical Discourse Analysis - Lioni, Shilva; Najma, Eva; Kurniawan, Afel; Athaya, Randy; Rianto, Alma Fathiinah (Vivid: Journal of Language and Literature, 2025)
Advertisement is one of the media which is used to influence audiences, which in this case is on framing woman portrayal or sharing feminism perspective and ideology. The goal of this study is to examine the portrayal of feminism in Nikewomen, What a girls made of advertisement. The research analyze a Nikewomen, What a girl made of advertisement by using Multimodal Critical Discourse Analysis (MCDA). The findings revealed that the what a girls made of advertisement symbolizes feminism ideology, as shown by the plot, text, color, and woman character used on the advertisement which have the freedom to express herself and as the symbol of strength, confidence, power, independence, and resilience. Furthermore, the video depicts feminism ideology by depicting woman superiority and highlighting woman as valuable creature. Nike impact audiences by messages given, which are a feminist concept and feminism ideology, through using advertisement videos as a platform to influence audiences. Generally, this research is qualitative descriptive-explorative research where descriptive and explorative are intended to describe and explain the situation based on collected data and facts, which are then analyzed and arranged systematically to get conclusions in detail to be a hypothesis.